Use of Images and Clinical Experience to Calibrate Dental Surgeons for the Diagnosis of Molar Incisor Hypomineralization - Heloisa Aparecida Orsini Vieira; Lisa Danielly Curcino Araújo; Fabrício Kitazono de Carvalho; Alexandra Mussolino de Queiroz; Francisco Wanderley Garcia Paula-Silva (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate an imaging protocol for use as a diagnostic and calibration tool for dentists before and after practical activity. Material and Methods: Thirty photos of children's teeth with or without changes in dental enamel were selected and evaluated by a group of experienced dentists previously calibrated to establish the diagnosis defined as the gold standard. After instructions, the images were shown to a group of postgraduate dentists for free identification of dental changes. Subsequently, a lecture on molar incisor hypomineralization (MIH) was carried out, and, at 14 days and all calibration was performed using the criteria previously. The retest was performed at 28 days. After experience in clinical activity in the following two weeks, the post-test was performed at 49 days.  Data were analyzed using Cohen's kappa coefficient. Results: Theoretical learning on the subject showed low inter-examiner agreement when the diagnosis of defects was made from images obtained from intraoral photographs. After clinical practice, there was greater intra-examiner agreement.  After theoretical training, dentists started to identify different types of enamel alteration, although with low agreement between them. Conclusion: Clinical experience in theoretical and imaging training favored the identification of defects. However, it is necessary to improve the protocol to establish a reliable and viable diagnostic method for calibration in MIH.